KELIMPAHAN ZOOPLANKTON PADA KOLAM TANAH GAMBUT TERHADAP PEMBERIAN AMELIORAN FORMULASI - Ramadinal Riski Lubis; Saberina Hasibuan; Syafriadiman Syafriadiman (Berkala Perikanan Terubuk, 2017)
This research was conducted on Maret–April 2016 at Petani Nenas st.  Kualu Nenas village, Districts Tambang, District Kampar, Riau. It’s was aimed to ofthis researchwas to determine the effect of formulation ameliorant zooplankton abundance paet soil pool. The method used was an experimental methodbyusing acompletely randomized design (CRD) with one factor, six treatments and threereplications.Treatments applied were P0:without ameliorant, P1:formulation ameliorant dose 400 g/m2, P2:formulation ameliorant dose 600 g/m2, P3: formulation amelioran dose 800 g/m2, P4: formulation amelioran dose 1000 g/m2, P5: formulation amelioran dose 1200 g/m2. Based on the research  results showed that got 9 zooplankton species from 4 classes that: Protozoa, Rotatoria, Crustacea, dan Insecta. classes protozoa is 4species, than Rotatoria class1species, Crustacea class 3 species, and Insecta class 1species. The zooplankton species that got is Coccomonassp,Euglena sp, Ochromonas sp, Pleodarina sp, Keratella cochlearis, Cyclops sp, Daphnia sp, Moina sp dan Culex. Zooplankton abundance best is P5 with abundance to 170136 ind/l.